Is Ageism Natural, Biological, or a Social Construct ? - Lamichhane, Pradip (Bodhi: An Interdisciplinary Journal, 2024)
This paper focuses on the study of ageism, a widespread and pervasive form of discrimination based on human age. Ageism, like racism and sexism, is practiced and performed mostly toward older adults through negative stereotypes and discriminatory language, behavior, and perceptions. Systematic inquiry, close observation, and extensive study are essential to identify, explore, and describe the roots, development process, and global spread of ageism. We cannot escape from the rampant consequences of ageism by taking it as a natural process or a social construct alone. This research paper, using qualitative data based on content analysis, aims to create knowledge on age-based discrimination by reviewing the existing literature. It redefines and interprets ageism in detail, including the types, causes, and consequences of ageism, and also suggests some measures to address the issues of ageism. As a research work, it concludes that ageism is stretching its roots in society, as intergenerational discrimination is evident in human language, socio-cultural practices, human roles and identities, and institutional practices in perceiving and treating adults.